Secondary immunodeficiency in lymphoproliferative malignancies. Issue 3 (12th July 2016) - Friman, Vanda; Winqvist, Ola; Blimark, Cecilie; Langerbeins, Petra; Chapel, Helen; Dhalla, Fatima
Abstract: Secondary immunodeficiencies occur as a consequence of various diseases, including hematological malignancies, and the use of pharmacological therapies, such as immunosuppressive, anti‐inflammatory, and biological drugs. Infections are the main cause of morbidity and mortality in multiple myeloma (MM) and chronic lymphocytic leukemia (CLL) patients. Recent advances in treatment have prolonged the duration of remission and the time between relapse phases in MM and CLL patients. However, managing multiple relapses and the use of salvage therapies can lead to cumulative immunosuppression and a higher risk of infections. The pathogenesis of immune deficiency secondary to lymphoproliferative malignancy is multifactorial including disease‐ and treatment‐related factors. Supportive treatment, including early vaccination, anti‐infective prophylaxis, and replacement immunoglobulin, plays a key role in preventing infections in MM and CLL. This article provides an overview of the basic immunology necessary to understand the pathogenesis of secondary immunodeficiency and the infectious complications in MM and CLL. We also discuss the evidence supporting the role of prophylactic replacement immunoglobulin treatment in patients with antibody failure secondary to MM and CLL and the indications for its use. Copyright © 2016 John Wiley & Sons, Ltd.